PELATIHAN PENYUSUNAN LAPORAN KEUANGAN UNTUK AGEN PT. POS INDONESIA (MOJOKERTO) GUNA PENGAJUAN KUR - Risawatie; Nurul Azizah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
So far, entrepreneurs have only focused on how to run an effective marketing strategy so that their business gets maximum sales results. In fact, business success is not only supported by a good marketing strategy. Often overlooked by novice entrepreneurs is managing finances neatly in the form of financial reports. Financial reports aim to monitor business results from time to time. Starting from monitoring the amount of turnover, profit and loss, the number of bills to be paid, tax invoices, etc. However, the reality is that many entrepreneurs only focus on marketing strategies and neglect their business financial statements. In fact, if entrepreneurs do not have good financial reports, they do not have real data to evaluate the development of their business. Thus, there is a high risk of leakage of funds, swelling of unwanted expenses, etc. This activity is designed to produce a financial report format. The object of this research is the Agent Owner of PT. Pos Mojokerto, which is engaged in mail and goods delivery services, online payments, philatelli and others. So that errors in preparing financial statements do not occur, entrepreneurs are required to make financial statements in accordance with Financial Accounting Standards (SAK) applicable in Indonesia.